1993
DOI: 10.2482/haigan.33.323
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Operative Procedure and Prognosis of Patients with Interlobar Invading Lung Cancer Lesions.

Abstract: General Hospital* A total of 65 patients who had interlobar invading lung cancer lesions underwent surgical resection. The 5-year survival rate of these cases was 42%. Of the 65 patients, the 52 patients who were treated with complete resection had a significantly higher survival rate than the 13 patients who underwent incomplete resection (52% vs. 0%). Of the 52 patients who were treated with complete resection, the 5-year survival rate of the 28 patients who underwent lobectomy of the invaded lobes (Group A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Sagawa et al reported that survival was worse after a lobectomy with a partial resection than after a bilobectomy. 11 Sensaki et al showed that local recurrence was observed in patients after a lobectomy with a partial resection but was not seen in patients after a bilobectomy. 7 Meanwhile, Morita et al and Okada et al described that postoperative survival did not differ between patients who received a lobectomy with a partial resection and those with either a bilobectomy or pneumonectomy.…”
Section: Discussionmentioning
confidence: 97%
“…Sagawa et al reported that survival was worse after a lobectomy with a partial resection than after a bilobectomy. 11 Sensaki et al showed that local recurrence was observed in patients after a lobectomy with a partial resection but was not seen in patients after a bilobectomy. 7 Meanwhile, Morita et al and Okada et al described that postoperative survival did not differ between patients who received a lobectomy with a partial resection and those with either a bilobectomy or pneumonectomy.…”
Section: Discussionmentioning
confidence: 97%
“…More than 25 years ago, 2 studies from Japan reported increased local recurrence rates and worse survival with PSR compared with MR for cases in which tumor crossed into another lobe. 8,9 Concluding differently, Nonaka and colleagues 10 in 2005 described no difference in local recurrence or postoperative prognosis between bilobectomy or pneumonectomy and lobectomy with partial resection in a group of 50 patients from a cohort of 322 patients with primary lung cancer.…”
Section: Commentmentioning
confidence: 99%